Global conformation of the Rag GTPase heterodimer governs eukaryotic amino acid sensing - Dylan D. Doxsey; Kuang Shen (Proceedings of the National Academy of Sciences, 2025)
The Rag GTPase heterodimer is a central mediator of amino acid sensing in eukaryotic cells. When amino acids are abundant, it binds to the mechanistic target of rapamycin complex 1 to activate cellular programs for growth and proliferation. In its functional cycle, besides local conformational changes near the nucleotides that are commonly observed in monomeric signaling GTPases, the relative positioning of the two Rag subunits, i.e., the global conformation, is unique due to the heterodimeric architecture. Although various global conformations have been captured in static structural models, dynamic transitions between these conformations and their biological relevance remain unclear. Here, we visualize the global conformation of the Rag GTPase heterodimer using single-molecule Förster resonance energy transfer. By tracking the movement of individual protein molecules, we found that the two subunits explore a wide conformational space, which is strictly dictated by the bound nucleotides, regulators, and mutations. Additionally, we demonstrate that proper modulation of the global conformation is crucial for correctly interpreting amino acid signals. Our results defined a checkpoint of amino acid sensing in eukaryotic cells.